ANALISIS PERHITUNGAN, PENYETORAN DAN PELAPORAN PAJAK PERTAMBAHAN NILAI (PPN) PADA PT. EMIGAS SEJAHTERA - Santoso, Fadhlurrahmah; Sondakh, Jullie J.; Gerungai, Natalia Y. T. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The aim of this research was to know whether the Value Added Tax calculation, subsmission and reporting at PT. Emigas Sejahtera, was suitable with the Law No. 42 Years 2009 about Value-Added Tax and Luxuries Tax. This type of research is descriptive with qualitative approach. The data collecting techniques done were interview and documentation. The steps taken to analyze the acquired data were done in two phases, they were (1) analyzing the Value-Added Tax in debt calculation based on the Law No. 42 Tahun Years 2009 aboutÂ  Value-Added Tax and Luxuries Tax, and (2) analyzing the Value-Added Tax subsmission and reporting based on the Law No. 42 Years 2009 about Value-Added Tax and Luxuries Tax. The result of the research showed that the Value-Added Tax calculation was suitable with the Law No. 42 Years 2009 about Value-Added Tax and Luxuries Tax. While for VAT subsmission and reporting, PT. Emigas Sejahtera has been delayed in subsmission and reporting Value-Added Tax.Keywords: Calculation, Subsmission, and Reporting VAT